Answer:
![(x+1)(x-3)=0\\x=-1,3\\√(2(-1)+3)=-1\\ √(1)=-1\\ √(2(3)+3)=3\\ √(9)=3\\](https://img.qammunity.org/2023/formulas/mathematics/high-school/n6xkr89strq8bg0uksxjsbssty6p30dfo2.png)
There are no extraneous solutions
Explanation:
To solve this equation, first we want to cancel out the radical;
![(√(2x+3) )^2=x^2; 2x+3=x^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/g53hhy37extk7ir1d1cvv1l4ddd0az001g.png)
Now that the equation looks simpler, we can slide 2x+3 to the other side to create a polynomial that we can factor;
![x^2-2x-3=0\\(x+1)(x-3)=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/xq5f47top0mqityo3govcy388k85x2nbtc.png)
You can check for extraneous solutions by plugging the answers in, which I showed above.